A randomized, controlled trial of oxycodone versus placebo in patients with postherpetic neuralgia and painful diabetic neuropathy treated with pregabalin - Zin, Che Suraya; Nissen, Lisa M.; O'Callaghan, James P.; Duffull, Stephen B.; Smith, Maree T.; Moore, Brendan J. (Elsevier, 2010)
The aim of this randomized double-blind, placebo-controlled, parallel-group study was to evaluate the efficacy, safety, and tolerability of pregabalin in combination with oxycodone or placebo, in patients with either postherpetic neuralgia (PHN) or painful diabetic neuropathy (PDN). After a 7-day washout period, 62 patients were randomized to receive either oxycodone mixture 10 mg/day or placebo mixture for 1 week. Patients were then started on open-label pregabalin (75, 150, 300 and 600 mg/day) according to a forced titration dosing regimen, while continuing the same dosage of oxycodone or placebo for 4 weeks. The primary efficacy measure was a decrease in the pain-intensity score of at least 2cm and a pain score <4cm measured using a 10-cm visual analogue scale (VAS) following pregabalin dosage escalation and treatment for 4 weeks. Secondary efficacy measures included sleep interference and the Neuropathic Pain Scale. There were similar levels of overall efficacy between pregabalin/oxycodone and pregabalin/placebo groups in relieving PHN and PDN related pain. PERSPECTIVE: Peripheral neuropathic pain presents commonly in clinical practice, and 2 of its most prevalent types are PHN and PDN. Currently available treatments provide some degree of pain relief in approximately 40-60% of patients, leaving the remainder with unremitting pain. Although this study supports the effectiveness of pregabalin in the treatment of PHN or PDN, it also shows that the addition of a low dose of oxycodone at 10mg/day does not enhance the pain-relieving effects of pregabalin.